Primary Leiomyosarcoma of the Mandibular Gingiva - Stylianos N Zanakis; Vasileios Lyris; Sotirios Kyriakou; George Agrogiannis; Penelope Korkolopoulou (Global Journal of Cancer Therapy - Peertechz Publications, 2016)
Primary oral leiomyosarcomas are exceptionally rare lesions often associated with poor prognosis. We report a case of leiomyosarcoma arising in the anterior mandibular gingiva, which is a non-prevalent site of occurrence. Clinically, the tumor was far from being firm and solid as it is usually described in the literature. Light microscopy failed to confirm the true nature of the lesion on the biopsy specimen.